Opening doors : understanding college reading - Cortina, Joe.; Elder, Janet, 1947- (Boston : McGraw-Hill, 2005)
Part One: Orientation: Preparing and Organizing Yourself for Success in College Chapter 1: Making Yourself Successful in College Skills Doing What Successful Students Do Motivating Yourself Setting Your Goals Identifying Your Learning Style Managing Your Time Setting Up a Weekly Study Schedule Making the Most of Your Study Time Planning Further Ahead: Creating a Monthly Assignment Calendar and Using a Daily To Do List Creating Your Summary: Developing Chapter Review Cards Readings Selection 1-1: "Why Go To College?" from P.O.W.E.R. Learning: Strategies for Success in College and Life by Robert S. Feldman (Study Skills) *Selection 1-2: "Getting Ready for Prime Time: Learning the Skills Needed to Succeed Today and Tomorrow" from Understanding Business by Bill Nickels, Jim McHugh, and Susan McHugh Selection 1-3: "Saved" from The Autobiography of Malcolm X as told to Alex Haley (Literature) Chapter 2: Approaching College Reading and Developing a College-Level Vocabulary Skills Understanding the Reading Process Improving Your Reading Predicting as You Read Monitoring Your Comprehension Adjusting Your Reading Rate Developing a College-Level Vocabulary Using Context Clues Using Word-Structure Clues Using a Dictionary Pronunciation Key Understanding Denotations and Connotations of Words Understanding Figurative Language Creating Your Summary: Developing Chapter Review Cards Readings *Selection 2-1: "Music Revolution: Napster and Recording in the Digital Age: from the Dynamics of Mass Communication: Media in the Digital Age by Joseph R. Dominick (Mass Communication) Selection 2-2: "The Yellow Ribbon" by Pete Hamill (Literature) Selection 2-3: "A Whale of a Survival Problem" from The Nature of Life by John Postlethwait and Janet Hopson Chapter 3: Approaching College Assignments: Reading Textbooks and Following Directions Skills College Textbooks: A Process for Reading and Studying Effectively Step 1: Prepare to Read Step 2: Ask and Answer Questions to Enhance Your Reading Step 3: Review by Rehearsing the Answers to Your Questions Following Directions in Textbooks and on Tests Guidelines for Following Directions Example: Directions from a Textbook Example: Directions on a Test Creating Your Summary: Developing Chapter Review Cards Readings *Selection 3-1: "African Americans: The Struggle for Equality from The American Democracy by Thomas E. Patterson (Government) Selection 3-2: "Parenthood?" from Human Development by Diane E. Papalia and Sally Wendkos Olds (Human Development) Selection 3-3: "Art in the Service of Religion" from Living with Art by Rita Gilbert (Art Appreciation) Part Two: Comprehension: Understanding College Textbooks by Reading for Ideas Chapter 4: Determining the Topic and the Stated Main Idea Skills The Topic of a Paragraph What is the Topic of a Paragraph, and Why is it Important? Determining and Expressing the Topic The Stated Main Idea of a Paragraph What is a Stated Main Idea, and Why is it Important? Locating the Stated Main Idea Sentence How to Tell if you have Identified the Stated Main Idea Sentence How to Avoid Two Common Errors in Locating a Stated Main Idea Stated Overall Main Ideas in Longer Passages A Word about Standardized Reading Tests: Topics and Stated Main Ideas Creating Your Summary: Developing Chapter Review Cards Readings Selection 4-1: "The New Workforce: People with Disabilities" from Business Week by Michelle Conlin (Magazine Article) Selection 4-2: "Latinos: An Emerging Influence" from Sociology: An Introduction by Richard J. Gelles and Ann Levine (Sociology) Selection 4-3: "Muhammed" from The 100: A Ranking of the Most Influential Persons in History by Michael K. Hart (History) Chapter 5: Formulating Implied Main Ideas Skills Implied Main Ideas in Paragraphs What is an Implied Main Idea? Why is Formulating Implied Main Ideas Important? Formulating an Implied Main Idea Steps to Follow Three Formulas for Using Information in a Paragraph to Formulate the Main Idea Requirements for Correctly Formulated Main Idea Sentences Implied Overall Main Ideas in Longer Passages A Word about Standardized Reading Tests: Implied Main Ideas Creating Your Summary: Developing Chapter Review Cards Readings *Selection 5-1: "Identity Theft: You are at Risk" Information Synthesized from Internet Sources (Personal Finance) Selection 5-2: "The Changing Roles of Men and Women" from U.S. News and World Report by Merrill McLoughlin with Tracy L. Shryer, Erica E. Goode, and Kathleen McAliffe (Sociology) Selection 5-3: "Demography" from Sociology: An Introduction by Richard J. Gelles and Ann Levine Chapter 6: Identifying Supporting Details Skills Supporting Details in Paragraphs What are Supporting Details? Why are Supporting Details Important? Identifying and Listing Supporting Details Major and Minor Details, and How to Tell the Difference A Word about Standardized Reading Tests: Supporting Details Creating Your Summary: Developing Chapter Review Cards Readings *Selection 6-1: "Diabetes: A New Epidemic" from Core Concepts in Health by Paul Insel and Walton Roth (Health) Selection 6-2: "Communication Close-Up at Ben and Jerry's Homemade" from Business Communication Today by Courtland Bovee and John Thill (Business) Selection 6-3: From A Beginner's Guide to the World Economy by Randy Charles Epping (Economics) Chapter 7: Recognizing Authors' Writing Patterns Skills Patterns of Writing What are Authors' Writing Patterns? Why is Recognizing Writing Patterns Important? Recognizing Authors' Writing Patterns List Pattern Sequence Pattern Definition Pattern Comparison-Contrast Pattern Cause-Effect Pattern Avoid Seeing Everything as a List A Word about Other Writing Patterns Mixed Patterns A Word about Standardized Reading Tests: Authors' Writing Patterns Creating Your Summary: Developing Chapter Review Cards Readings Selection 7-1: "Career Choice: Choosing Your Own Future" from Personal Finance by Jack R. Kapoor, Les R. Dlabay, and Robert Hughes (Personal Finance) Selection 7-2: "The Decision to Marry" from Targeting Wellness: The Core by Marvin Levy, Mark Dignan, and Janet Shirreffs (Health) Selection 7-3: "Reactions to Impending Death" from Essentials of Psychology by Dennis Coon (Psychology) Chapter 8: Reading Critically Skills What is Critical Reading? Critical Reading Skills Determining an Author's Purpose and Intended Audience Determining an Author's Point of View, Tone, and Intended Meaning A Word about Standardized Reading Tests: Critical Reading Creating Your Summary: Developing Chapter Review Cards Readings *Selection 8-1: "Think Before You Speak: Public Speaking in a Multicultural World" from The Art of Public Speaking by Stephen E. Lucas (Speech Communication) Selection 8-2: From Having Our Say: The Delany Sisters' First 100 Years by Sarah and Elizabeth Delany with Amy Hill Hearth (Literature) Selection 8-3: From The Joy Luck Club by Amy Tan (Literature) Chapter 9: Thinking Critically Skills What is Critical Thinking, and Why Is It Important? Critical Thinking Skills Why Readers Fail to Think Critically Distinguishing Facts from Opinions and Determining Whether Opinions are Well Supported Making Inferences and Drawing Logical Conclusions Distinguishing between Deductive and Inductive Reasoning Evaluating an Author's Argument Identifying Propaganda Devices A Word about Standardized Reading Tests: Critical Thinking Creating Your Summary: Developing Chapter Review Cards Readings Selection 9-1: "Sport Utility Vehicles: How Do I Hate Thee? Let Me Count the Ways" from the Dallas Morning News by Geneva Overholser Selection 9-2: "Why Vote? Politicians Are All the Same" from American Politics in a Changing World by Janet Flammang, Dennis Gordon, Timothy Lukes, and Kenneth Smorsten (Government) Selection 9-3: "Take Out the Trash, and Put It...Where?" from Parade Magazine by Bernard Gavzer Part Three: Systems for Studying Textbooks: Developing a System That Works for You Chapter 10: Selecting and Organizing Textbook Information Skills Studying Better Rather Than Harder Three Keys to Studying College Textbooks Key 1: Selectivity Key 2: Organization Key 3: Rehearsal Using Textbook Features Prefaces Tables of Contents Part Openings Chapter Outlines Chapter Objectives and Introductions Lists and Sequences Boxes Tables Graphic Aids Vocabulary Aids Study Questions and Activities Chapter Summaries Appendixes Bibliographies, Suggested Readings, and Webliographies Indexes Additional Features and Supplements Marking Textbooks: Underlining, Highlighting, a nd Annotating Taking Notes from Textbooks: Outlining, Mapping, and Summarizing Guidelines for Outlining Guidelines for the Cornell Method of Note-Taking Guidelines for Mapping Guidelines for Summarizing Guidelines for Interpreting Graphic Material Bar Graphs Line Graphs Pie Charts Flowcharts Tables Creating Your Summary: Developing Chapter Review Cards Reading *Selection 10-1: "The Age of Globalization" from American History: A Survey by Alan Brinkley (History) Chapter 11: Rehearsing Textbook Information and Preparing for Tests Skills Rehearsal and Memory Studying for Tests General Guidelines Five-Day Test Review Plan Creating Review Cards to Prepare for a Test Creating Test Review Sheets Creating Your Summary: Developing Chapter Review Cards Reading *Selection 11-1: "Cultural Diversity: Family Strengths and Challenges" from Marriages and Families: Intimacy, Diversity, and Strengths by David Olson and John DeFrain Appendix 1: Glossary of Key Reading and Study Skills Terms Appendix 2: A List of Word Parts: Prefixes, Roots, and Suffixes Appendix 3: World Map, United States Map, and List of World Capitals Credits Index Vocabulary Log
Includes index.
Keywords: College readers; Reading (Higher education); Reading comprehension; Study skills; College readers